The Apoptosis Regulator 14-3-3η and Its Potential as a Therapeutic Target in Pituitary Oncocytoma - Zhao, Sida; Li, Bin; Li, Chuzhong; Gao, Hua; Miao, Yazhou; He, Yue; Wang, Hongyun; Gong, Lei; Li, Dan; Zhang, Yazhuo; Feng, Jie (Frontiers in Endocrinology, 2019)
The 14-3-3 protein family has attracted much attention in the pathogenesis of human tumors because of its involvement in tumorigenesis. In previous studies, we found that 14-3-3η was highly expressed in pituitary oncocytomas. However, the mechanism by which 14-3-3η regulates tumorigenesis in pituitary oncocytomas is unclear. 14-3-3η-binding proteins were investigated in pituitary oncocytomas by immunoprecipitation and proteomic analysis. A total of 443 proteins were identified as 14-3-3η binding proteins. The interactions of 14-3-3η and its binding partners were identified by a network analysis using the STRING database. The network included 433 nodes and 564 edges. PRAS40 (AKT1S1) was a binding protein of 14-3-3η and showed experimental interactions with 14-3-3η in the STRING database. The combined score was 0.407, which suggested a functional link. The 443 binding proteins of 14-3-3η showed enriched molecular signatures in the GSEA and GO analysis. PRAS40 (AKT1S1) was enriched in the mTOR signaling pathway. Western blot analysis showed that the relative expression of p-PRAS40 (T246)/PRAS40 was significantly higher in pituitary oncocytomas than in normal pituitary tissues (p<0.05). R18, an 14-3-3 protein inhibitor, inhibited MMQ cell proliferation after treatment with 8 µM R18 for 48 h compared to the control group (p<0.01). These results suggest that 14-3-3η may be involved in promoting tumorigenesis in pituitary oncocytomas by interacting with PRAS40 (T246) via the mTOR signaling pathway.